Addressing juvenile crime what have we learned, and how should we proceed? - Lane, Jodi (Criminology & public policy, 2018)
At‐risk and offending juveniles remain the most promising target group for crime reduction efforts. Many of the problems these youths faced in the 1960s remain or have intensified, and policies to address them have shifted. Yet, research on the causes, consequences, and best responses to juvenile crime has advanced considerably and provides important lessons for policy makers and practitioners moving forward. These include (a) help don't hurt; (b) provide better procedural protections; (c) continue to build, implement, and refine evidence‐based programming; (d) tailor services; (e) tackle community‐level problems; (f) really listen and work together; (g) build better data systems; and (h) invest resources in children and teens. Providing a retrospective on the 1967 U.S. President's Commission on Law Enforcement and Administration of Justice report, I briefly summarize and update the Commission's findings on factors related to juvenile delinquency, outline the Commission's policy recommendations, review the research on policy and practice changes since the report, and consider current implications for policy and practice.